Exhaust the exhausters: Targeting regulatory T cells in the tumor microenvironment - McRitchie, Bayley R.; Akkaya, Billur (Frontiers in Immunology, 2022)
The concept of cancer immunotherapy has gained immense momentum over the recent years. The advancements in checkpoint blockade have led to a notable progress in treating a plethora of cancer types. However, these approaches also appear to have stalled due to factors such as individuals’ genetic make-up, resistant tumor sub-types and immune related adverse events (irAE). While the major focus of immunotherapies has largely been alleviating the cell-intrinsic defects of CD8+ T cells in the tumor microenvironment (TME), amending the relationship between tumor specific CD4+ T cells and CD8+ T cells has started driving attention as well. A major roadblock to improve the cross-talk between CD4+ T cells and CD8+ T cells is the immune suppressive action of tumor infiltrating T regulatory (Treg) cells. Despite their indispensable in protecting tissues against autoimmune threats, Tregs have also been under scrutiny for helping tumors thrive. This review addresses how Tregs establish themselves at the TME and suppress anti-tumor immunity. Particularly, we delve into factors that promote Treg migration into tumor tissue and discuss the unique cellular and humoral composition of TME that aids survival, differentiation and function of intratumoral Tregs. Furthermore, we summarize the potential suppression mechanisms used by intratumoral Tregs and discuss ways to target those to ultimately guide new immunotherapies.